2006
DOI: 10.1111/j.1750-3841.2006.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acid Content of Selected Foods in an African‐American Community

Abstract: Trans fatty acid content was examined in several grocery foods and fast foods in an African‐American community. Food samples were selected based on the frequency of use among this population group in the local community. Samples were collected 3 times with an interval of 1 wk. Total fat content was analyzed by Soxhlet method. Fatty acids profile, including trans fatty acids, was analyzed by GC–MS. In grocery foods, no trans fatty acids were detected in fish sticks, salad dressing, mayonnaise, muffin, and potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
1
6
2
Order By: Relevance
“…In fact, the chips and fries, sauces and dressings, as well as ice cream products employed in the present study contained TFAs substantially lower than those reported by Aro and others (1998). The margarine products sampled in an African‐American community (Huang and others 2006) also contained higher TFAs (19.13%[w/w] of fat) than those investigated (averaging 5.1%). Conversely, the products sampled from New Zealand, including chips and fries, pie and cake, and wafer and biscuit products (Lake and others 1996), contained less TFAs than those reported in this study.…”
Section: Resultscontrasting
confidence: 56%
“…In fact, the chips and fries, sauces and dressings, as well as ice cream products employed in the present study contained TFAs substantially lower than those reported by Aro and others (1998). The margarine products sampled in an African‐American community (Huang and others 2006) also contained higher TFAs (19.13%[w/w] of fat) than those investigated (averaging 5.1%). Conversely, the products sampled from New Zealand, including chips and fries, pie and cake, and wafer and biscuit products (Lake and others 1996), contained less TFAs than those reported in this study.…”
Section: Resultscontrasting
confidence: 56%
“…A higher value of trans fat was determined in sample B-4 and a lower level in sample B-1. These values are higher than those reported in the literature [11,13,[18][19][20]. None of the analyzed samples were free from trans fatty acids.…”
Section: Samplescontrasting
confidence: 62%
“…[21][22][23][24] The result in this study was higher than previous reports. [27,28] In our study, TFA in potato crisps ranged from 0.02 to 1.35 g/100 g fatty acids. The use of totally hydrogenated fats for heating, frying, and deep frying leads to an increase in TFA values in the fried products.…”
Section: Resultsmentioning
confidence: 96%